Effect of Financial Leverage on the Trend of Stock Pricing Fluctuations in Companies Listed in Tehran Stock Exchange - Karimi, Goran (2020)
The key factor in creating value in companies and banks is the capital structure and financing method so that companies are moving towards creating value through debt control and the use of proper financing. Therefore, the present study was conducted to investigate the effect of financial leverage on the stock price volatility trend in listed companies in Tehran Stock Exchange for the period 2011-2018 using systematic elimination method. The results of data analysis showed that financial leverage capital has significant effect on the trend of stock price volatility in listed companies in Tehran Stock Exchange.